(De Facto) Historical Ethnic Borders and Land Tenure in Sub-Saharan Africa - Emilio Depetris-Chauvin; Ömer Özak (Institute of Labor Economics (IZA), 2023)
We study the role of proximity to historical ethnic borders in determining individual land ownership in Sub-Saharan Africa. Following an instrumental variable strategy, we document that individuals have a lower likelihood of owning land near historical ethnic borders. In particular, the likelihood of owning land decreases by 15 percentage points, i.e., about 1/3 of the mean rate of landownership, for rural migrants who move from 57km (90th percentile) to 2 km (10th percentile) from the border. This result aligns with the view that competition for land is stronger and property rights are weaker close to historical ethnic borders in Sub-Saharan Africa.
Keywords: D74; N57; O13; O17; O43; P48; Q15; Q34; 330; land ownership; borders; property rights; historical homelands; development; Africa; Voronoi Tessellation; Thiessen Tessellation